–3x + 1 + 10x = x + 4

Answers

Answer 1
Answer: -3x+1+10x=x+4
-3x+10x-x=4-1
6x=3
x=3/6=1/2

Answer: x=1/2

Related Questions

steps for patient medication decrease 25 mg per day for one week. Whats the change at end of the week?
Verify tanx + cotx = 1/ sinxcosx
Akiba Ellis deposits the following in her checking account: 6 five-dollar bills, 5 two dollar bills, 12 one dollar bills, 9 half dollars, 6 quarters, 42 dimes, 10 nickels, 15 pennies, and a check for $97.23. what is her total deposit?
Hilbert's axioms changed Euclid's geometry. True False
Which ordered pair would form a proportional relationship with the point graphed below?On a coordinate plane, point (negative 20, 40) is plotted.

What are the first three terms of the sequence represented by the recursive formula an=n^2-an-1 if a5=14 1/4

Answers

Answer:

B. 0.25, 3.75, 5.25

just convert what the person above said but into decimals

Answer:

  1/4, 3 3/4, 5 1/4

Step-by-step explanation:

Solving for a[n-1], we get ...

  a[n-1] = n^2 -a[n]

Then ...

  a[4] = 5^2 -a[5] = 25 -14 1/4 = 10 3/4

  a[3] = 4^2 -a[4] = 16 -10 3/4 = 5 1/4

  a[2] = 3^2 -a[3] = 9 -5 1/4 = 3 3/4

  a[1] = 2^2 -a[2] = 4 -3 3/4 = 1/4

Then the first three terms are a[1], a[2], and a[3]:

  1/4, 3 3/4, 5 1/4

If h(x)=x-7 and g(x)=x^ which expression is equivalent to (g•h)(5)?A) (5-7)^
B) (5)^-7
C) (5)^ (5-7)
D) (5-7)x^

Answers

Answer:

A (5-7)^

Step-by-step explanation:

We have the next two functions h(x)=x-7 and g(x)=x^. We need to find (g•h) that is equal to g(h(x)) then:

(g•h)=g(h(x))=(x-7)^

Finally in the poin x=5 we have:

(g•h)=g(h(x))=(x-7)^

(g•h)=g(h(5))=(5-7)^

Then the answer is A

Assuming that by ^, you mean ², here's how you do this:
(g•h)(5) means that you need to solve g(h(5)). So, you plug 5 in for x in h(x), then you plug the solution of that in for x in g(x) like so:
h(5)=5-7 \n g(h(5))= (5-7)^(2)

The answer is A. (5-7)
²

Hope this helps!

BRAINLIEST IF CORRECTThere are n gallons of oil. After m gallons have been used then, in terms of n and m, what percent of oil remains? What percent was used?

Answers

Answer:

Percent of Remaining Oil

= n-m/n x 100

Percent of Oil Used

m/n x 100

Answer:

Remaining Oil = ((n - m)/n) • 100

Percent Used = (m / n) • 100

Step-by-step explanation:

Is x+1 a factor of the function f(x)=2x⁵-4x⁴+9x³-x+13?Show work supporting your answer.

Answers

Answer:

(x+1) will not be factor of given polynomial

Step-by-step explanation:

We have given polynomial f(x)=2x^5-4x^4+9x^3-x+13

We have to find that  is (x+1) factor of the given polynomial

If (x+1) will be the factor of the polynomial then x= -1 will be the root of the polynomial

And if we put x =-1 in the pronominal then then its value will be zero

f(-1)=2(-1)^5-4(-1)^4+9(-1)^3-(-1)+13=-2-4-9+1+13=-1

So (x+1) will not be factor of given polynomial

10+3(2xz+3y)2xz what's the answer.

Answers

10+3(2xz+3y)\cdot 2xz=10+(6xz+9y)\cdot 2xz=\n \n=10+12x^2z^2+18xyz

Use synthetic division to solve (x^4 – 1) ÷ (x – 1). What is the quotienta. x^3-x^2+x-1
b. x^3
c.x^3+x^2+x+1
d. x^3-2

Answers

Answer:

Option C.

Step-by-step explanation:

We have to solve (x^(4)-1 )/(x-1) by synthetic division and tell the quotient.

First we will write the numerator in the standard form as ax^(4)+bx^(3)+cx^(2)+dx+e

Which will become as 1.x^(4)+0.x^(3)+0.x^(2)+0.x^(1)-1

Since denominator of the fraction is (x -1) therefore we take x = 1 as zero root.

Now we form the synthetic form as below

          1        0      0    0      -1

1          1        1       1      1      0

          x³      x²      x    

Here coefficient of x³ is 1, for x² is 1, for x is 1, and constant term 1.

Now the fraction will come in the form of  

(x -1) + ((1.x^(3)+1.x^(2)+1.x+1))/((x - 1))

Therefore quotient will be x^(3)+x^(2)+x+1

Option C. is the answer

Hello,

x^4-1=(x²-1)(x²+1)=(x²+1)(x-1)(x+1)
==>(x^4-1)/(x-1)=(x²+1)(x+1)=x^3+x^2+x+1
Answer C